Assessment CDT and Lipid Profile in Rats Undergo Bile Duct Ligation - Fahad Najd Obaid, Haider Salih Jaffat, Mohsin Abdulhussein Hasan, Abdul Latif Al Bayaa (Revista Electronica de Veterinaria, 2022)
The study was shown by the research laboratories of the Department of Biology / Faculty of Science/ University of Kufa for a period for six months, 40 male rats were used and were divided into three groups; Group A: male rats administered with drinking water as negative control (N. C.) Group B: male rats undergo Bile duct ligation for one week, At the end of the treatment period, male rats were sacrificed and blood samples were obtained for assessment of (CDT levels and levels of T.C, T.G., LDL and  VLDL) .The result has no significant change (p > 0.05) in the level of CDT, and then lipid profile levels show a significant elevate in cholesterol, TG, VLDL, and LDL in rats undergoing BDL compare to control groups.